2014
DOI: 10.1111/jftr.12039
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality as the “New” Critical Approach in Feminist Family Studies: Evolving Racial/Ethnic Feminisms and Critical Race Theories

Abstract: This article presents one of the first comprehensive reviews of intersectionality literature for a family studies audience. The purpose of this article is manifold: (1) to review the interdisciplinary scholarship on intersectionality as a theoretical approach, paradigm, or method; (2) to review methodological considerations using intersectionality as a theoretical guide to conduct research; and (3) to examine how contemporary family scholars are utilizing an intersectional approach to examine the complexities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
231
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(244 citation statements)
references
References 66 publications
3
231
0
2
Order By: Relevance
“…This approach, originally based in critical race theory and feminist theory (Few-Demo, 2014), is critical of researchers’ tendency to consider a social category, such as African Americans, to be homogeneous, when in fact members of that category vary substantially on other dimensions such as social class and gender. In the research reported here, we consider the intersection of race and social class.…”
Section: Intersectionalitymentioning
confidence: 99%
“…This approach, originally based in critical race theory and feminist theory (Few-Demo, 2014), is critical of researchers’ tendency to consider a social category, such as African Americans, to be homogeneous, when in fact members of that category vary substantially on other dimensions such as social class and gender. In the research reported here, we consider the intersection of race and social class.…”
Section: Intersectionalitymentioning
confidence: 99%
“…At the same time, poststructuralists' skepticism of categories makes us hesitate to delineate a category of women because of the ways binary categories of men/women are limiting devices. Moreover, we also are aware that much theorizing and empirical work based on the category of “women” has been limited to White, middle‐class heterosexual women's experiences (Few‐Demo, ).…”
Section: Accounting For Feminism In Our Research: Epistemology Agendmentioning
confidence: 99%
“…Despite years of debunking a deficit perspective that privileges the White, middle‐class, heterosexual, married family as the standard‐bearer (Smith, ), the idealized image of the family remains evident in research, policy, and public thought. The structural organization of power and oppression is a particular area where intersectionality, critical race theory, and feminist perspectives can enhance the understanding of family diversity (Few‐Demo, ). In the epilogue, Coontz joins the conversation about the differential impacts of gender, race, class, sexual orientation and the like on family processes and outcomes through interventions in the areas of education, resource allocation, family roles, work–family conflict, and reproductive policies.…”
Section: Incorporating Intersectionalitymentioning
confidence: 99%